Kinetic modeling of the biodiesel production process using neem seed oil: An alternative to petroleum-diesel - Oyegoke, Toyese; Ibraheem, Kazeem Ajadi (European Journal of Chemistry, 2021)
Promoting the green technology campaign that would actualize a biorefinery establishment and would promote cleaner fuel production and air in our environment. This study carried out kinetics studies of biodiesel production over a mixed oxide, Ca-Mg-O catalyst, providing relevant kinetics parameters. This study indicated that biodiesel production is a zero-order reaction, a process independent of the concentration. The results obtained from this study confirm the activation energy, Ea, of the reaction to be 406.53 J/mol, while the pre-exponential factor A was found to be 0.01618 1/min (or 0.9 1/h). Other are kinetics models that were developed for the prediction of the reaction kinetics for the production process is also reported in this study. The findings reported in this study would go a long way to facilitate the modeling, simulation, and design of the biodiesel production process.